Community Behavior in Health Protocol Policy Perspective Post Covid-19 Vaccination - Beni Hartanto; Deni Sudrajat; Tine Badriatin (Program Studi Administrasi Negara Universitas Serang Raya, 2021)
The spread of COVID-19 has an impact on various aspects of life, not only material losses but has claimed many millions of lives. Each country has made various policies in tackling and further outbreaks of the virus. The government has issued policies related to health protocols to solutions by vaccinating the entire community, but after vaccination many people ignore health protocols. This study is a descriptive study with the aim of describing people's tasikmalaya city behavior after vaccination and viewed from a policy perspective on health protocols. Based on research, it shows that people who have vaccinated both stages one and two, pay less attention to health protocols, especially in using masks, as well as the increasing number of people's activities that ignore health protocols, coupled with weak supervision from each Regional Government with the Covid-19 task force so that the community is more lax to carry out various activities without paying attention to the applicable provisions